The Relationship between Anti-dsDNA Antibody Levels and Clinical Manifestationin Systemic Lupus Erythematosus Patients - Noviantoro Sunarko (Indonesian Journal of Rheumatology, 2022)
Background: Anti-double-stranded deoxyribonucleic acid (anti-dsDNA)antibodies have been long known as specific autoantibodies in systemiclupus erythematosus (SLE) patients. Their central role in the pathogenesisof SLE also had been proposed for a long time. But many studies have failedto show a consistent association between anti-dsDNA levels and clinicalmanifestation in SLE patients. This phenomenon raised controversies aboutanti-dsDNA’s role in the development of the disease. This study aimed to givemore description of the relationship between anti-dsDNA antibodies leveland clinical manifestation of SLE. Methods: This study took place in Dr.Sardjito General Hospital, Yogyakarta, Indonesia, from July 2017 to July2020. This study is a descriptive-analytic study with a cross-sectionaldesign. Sixty-three females with new cases of SLE were included in thisstudy. We used Alegria® ORGENTEC ORG204S kits to measure anti-dsDNAantibody levels in those patients. All organ involvement and anti-dsDNA leveldata were collected from the subject’s medical record. We categorized thepatient into two groups, one group with a high level of anti-dsDNA antibodiesand the other with the normal one. The statistical analysis was conductedby using the chi-square test to associate the anti-dsDNA antibodies level withthe clinical manifestation of SLE that developed in those patients. Results:The haematological manifestation was the most prevalent clinicalmanifestation of SLE (69.8%), followed by cutaneous (66.7%) andmusculoskeletal manifestation (63.5%), respectively. Thirty subjects had ahigh level of anti-dsDNA, and 33 subjects had the normal one. Anti-dsDNAantibody levels were only significantly associated with the development ofhaematological manifestation (p=0.026). Conclusion: Haematologicalmanifestation tends to develop in SLE patients with high anti-dsDNAantibody levels.